Design and Methodology for the Korean Observational and Escitalopram Treatment Studies of Depression in Acute Coronary Syndrome: K-DEPACS and EsDEPACS - Kim, Jae-Min; Bae, Kyung-Yeol; Kang, Hee-Ju; Kim, Sung-Wan; Shin, Il-Seon; Hong, Young-Joon; Kim, Ju-Han; Shin, Hee-Young; Ahn, YoungKeun; Kim, Jong-Keun; Jeong, Myung-Ho; Yoon, Jin-Sang (Psychiatry investigation, 2014)
Depression is common after acute coronary syndrome (ACS), adversely affecting cardiac course and prognosis. There have been only a few evidence-based treatment options for depression in ACS. Accordingly, we planned the Korean Depression in ACS (K-DEPACS) study, which investigated depressive disorders in patients with ACS using a naturalistic prospective design, and the Escitalopram for DEPACS (EsDEPACS) trial, which assessed the efficacy and safety of escitalopram for treating major or minor depression in patients with ACS. Participants in the K-DEPACS study were consecutively recruited from patients with ACS who were recently hospitalized at Chonnam National University Hospital, Gwangju, South Korea. Diagnoses were confirmed by coronary angiography from 2005. Data on depressive and cardiovascular characteristics were obtained at 2 weeks, 3 months, 12 months, and every 6 months thereafter following the index ACS admission. The K-DEPACS participants who met the DSM-IV criteria for major or minor depressive disorder were randomly assigned to groups in the 24-week, double-blind, placebo-controlled EsDEPACS trial beginning in 2007. The outcome of treatments for depressive and other psychiatric symptoms, issues related to safety, including general adversity, and cardiovascular factors were assessed. The K-DEPACS study can significantly contribute to research on the complex relationships between depression and ACS. The results of the EsDEPACS trial provide an additional treatment option for clinicians treating these patients.